Static domain wall in braneworld gravity - Abdalla, M. C. B. [UNESP]; Carlesso, P. F. [UNESP]; Hoff da Silva, J. M. [UNESP] (Springer, 2014)
In this paper we consider a static domain wall inside a 3-brane. Different from the standard achievement obtained in General Relativity, the analysis performed here gives a consistency condition for the existence of static domain walls in a braneworld gravitational scenario. Also the behavior of the domain wall's gravitational field in the newtonian limit is shown.